2010
DOI: 10.1007/s10551-010-0669-9
|View full text |Cite
|
Sign up to set email alerts
|

A Stakeholder Identity Orientation Approach to Corporate Social Performance in Family Firms

Abstract: corporate social performance, family firms, stakeholder theory,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
221
2
22

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(261 citation statements)
references
References 92 publications
(106 reference statements)
11
221
2
22
Order By: Relevance
“…It also qualifies the results of other empirical studies, notably those of Uhlaner et al (2012) [96], who, based on a sample of small-and medium-sized Dutch businesses, showed a conditional influence of family businesses on their commitments, which favored environmentally-friendly practices. Similarly, while the study by [13], on a sample of large, publicly-traded S&P 500 companies, partially confirms our hypotheses, it also suggests that in North America there is a positive relationship between family businesses and some dimensions of CSR-in particular those related to community initiatives and employee relations. Their results suggested that the effect increases with the level of family involvement in the business.…”
Section: Contributionssupporting
confidence: 74%
See 2 more Smart Citations
“…It also qualifies the results of other empirical studies, notably those of Uhlaner et al (2012) [96], who, based on a sample of small-and medium-sized Dutch businesses, showed a conditional influence of family businesses on their commitments, which favored environmentally-friendly practices. Similarly, while the study by [13], on a sample of large, publicly-traded S&P 500 companies, partially confirms our hypotheses, it also suggests that in North America there is a positive relationship between family businesses and some dimensions of CSR-in particular those related to community initiatives and employee relations. Their results suggested that the effect increases with the level of family involvement in the business.…”
Section: Contributionssupporting
confidence: 74%
“…This addresses the psychological factors at work, through the overlap between organizational and individual identity (Hogg, 2003 [63]; Hogg and Terry, 2001 [64]). The authors of [13] use the theory of organizational identity (Albert and Whetten, 1985 [65]) to explain the CSR of family businesses: such businesses orient their identity towards their stakeholders. Non-family firms make fewer engagements to socially responsible activities and only to the extent that they match individual identities.…”
Section: Proactive Stakeholder Engagement (Pse) and Socioemotional Wementioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that these findings could be affected by the family involvement in active management; therefore, it is of interest to estimate the effect of different levels of involvement. Several authors suggest that the extent of family involvement shape a firm's attitude towards social and environmental responsible activities and generate heterogeneity among family businesses [69][70][71]. Bingham et al [69] assert that increased levels of family involvement bring a collectivistic orientation towards stakeholders as non-economic objectives, such as endorsing the ethical values shared and perpetuated by the family members [71], become more important [30,45].…”
Section: H1mentioning
confidence: 99%
“…Several authors suggest that the extent of family involvement shape a firm's attitude towards social and environmental responsible activities and generate heterogeneity among family businesses [69][70][71]. Bingham et al [69] assert that increased levels of family involvement bring a collectivistic orientation towards stakeholders as non-economic objectives, such as endorsing the ethical values shared and perpetuated by the family members [71], become more important [30,45]. This transgenerational perspective is enhanced by the presence of the founder in active management [72] who plays a relevant role in the adoption of this collectivistic orientation, enhancing the firm's activism towards the community, employees and the supplying of quality products and services to consumers [69].…”
Section: H1mentioning
confidence: 99%